Kombucha tea from ambarella fruit as a natural antibacterial agent against Escherichia Coli and Staphylococcus aureus - Musyirna Rahmah Nasution; Agfa Febriyananda (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2025)
Kombucha tea is a traditional fermented beverage known for its probiotic benefits, produced from sweetened tea fermented with a Symbiotic Culture of Bacteria and Yeast (SCOBY). Recent innovations have focused on enhancing its functional properties using local fruit extracts. However, studies on the incorporation of Spondias dulcis (kedondong), a native fruit of Riau, remain limited. This study aims to formulate kombucha tea enriched with kedondong juice and evaluate its quality and antibacterial activity against Escherichia coli and Staphylococcus aureus. Four formulations were prepared with kedondong juice concentrations of 0% (F1), 10% (F2), 20% (F3), and 30% (F4). Parameters observed included organoleptic properties, pH, alcohol content, microbial growth, and total acidity. Antibacterial activity was tested using the disc diffusion method, and results were statistically analyzed using One-Way ANOVA. F4 on day 7 showed the highest inhibition zones (13.30 mm for E. coli and 14.49 mm for S. aureus), with significant differences between formulations (p < 0.05). This study highlights the potential of kedondong-enriched kombucha tea as a functional probiotic beverage and a natural source of mild antibacterial agents, offering an innovative approach to utilizing local biodiversity in public health.